Epidermoid renal cyst: an unusual finding - Rathod, Dharmendra Rameshbhai; Bhatt, Jayprakash Gunvantrai; Khakkhar, Riddhi Vivekbhai; parmar, Pratyush virjibhai (Annals of Pathology and Laboratory Medicine, 2014)
This report describes a case of epidermoid cyst affecting the left kidney of a 52-year-old female. The condition was accidentally discovered during the histopathology examination. Patient presented with complain of burning micturition, nausea, vomiting and fever for 15 days. Grossly, the kidney was distorted cyst like that was filled with a cheesy material. The histological picture of non-functioning kidney was apparent in the compressed renal parenchyma by the cyst that was identical to an epidermoid cyst. In conclusion, although rare, epidermoid cyst of the kidney could cause serious kidney damage leading to a non-functioning of kidney. Epidermoid cyst of the kidney could be multiple, producing a picture similar to hydronephrosis and broadening the differential diagnosis of multicystic disease of the kidney. Timely diagnosis is essential to prevent radical surgery.